1984
DOI: 10.1007/bf01711377
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation for acute leukemia in second or subsequent remission

Abstract: Twenty-one patients with acute leukemia in second to fifth remission were treated with bone marrow transplantation: 19 patients with transplants from HLA-matched siblings and two with transplants from identical twins. Twelve patients survived from 15 to 1,625 days after transplantation: six of 11 in the ALL group and six of 10 in the AML group. Recurrence of leukemia after marrow transplantation occurred in five patients. The cause of death in five patients was infection, in two patients combined with graft-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
3

Year Published

1985
1985
2000
2000

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
1
0
3
Order By: Relevance
“…7,8 However, few studies reporting a large enough sample of patients to determine prognostic factors have been reported. [13][14][15][16][17] To our knowledge, this study is the largest cohort of patients with an advanced stage of AML undergoing allogeneic HSCT. We have shown that factors over which we have total, some, or no control can influence survival duration, risk of relapse and TRM after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, few studies reporting a large enough sample of patients to determine prognostic factors have been reported. [13][14][15][16][17] To our knowledge, this study is the largest cohort of patients with an advanced stage of AML undergoing allogeneic HSCT. We have shown that factors over which we have total, some, or no control can influence survival duration, risk of relapse and TRM after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Zus/itzlich wurde das Transplantat bei hinreichender Zellzahl (mehr als 2 x 10 s mononukle/ire Zetten/kg K6rpergewicht) mit Anti-Human-T-Zell-Globulin (AHTCG) vorinkubiert [64]. Bez/iglich der Einzelheiten und Dosierung wird auf die fr/iheren Berichte ve~Tiesen [56,87]. Ab KMT Nr.…”
Section: Gvhd-prophylaxe Und Therapieunclassified
“…38 wurden alte Patienten bei einem Alter gr613er als 10 Jahre prophylaktisch mit Cyclosporin A behandelt, die Applikation erfolgte intraven6s vom Tag -I 0 bis + 20, nachfolgend oral. Zu Einzetheiten der Cyclosporin A-Dosierung und Reduktion bei entsprechenden Nebenwirkungen wird auf den fr/iheren Bericht verwiesen [56]. Die Therapie einer akuten GvHD erfolgte nach einer Hautbiopsie mit Prednisolon in einer Dosierung von 1-2 mg/kg K6rpergewicht bei den klinischen Schweregraden I u n d II, bei Grad III und IV kurzfristig mit 10-20 mg/kg K6rpergewicht Prednisolon intraven6s.…”
Section: Gvhd-prophylaxe Und Therapieunclassified
See 1 more Smart Citation